PENERAPAN PEMBELAJARAN DIFERENSIASI UNTUK MENGOPTIMALKAN PERKEMBANGAN ANAK USIA DINI PAUD KUNCUP MELATI - Wijaya, Pipit Rika; A Zulkarnain Ali; Ade Irma Novianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of differentiated instruction to optimize early childhood development at PAUD Kuncup Melati. Differentiated instruction is an approach that tailors content, process, and product based on children’s readiness, interests, and learning profiles. This research employs a qualitative approach with a case study method. Data were collected through participatory observation, structured interviews, and documentation. The findings indicate that the application of differentiated instruction at PAUD Kuncup Melati enhances children's engagement in learning and positively impacts their cognitive, socio- emotional, and motor development. Children were observed to be more active, confident, and able to learn according to their individual characteristics. Challenges include limited teacher competencies, inadequate facilities, and parental expectations that are not aligned with differentiated practices. Therefore, ongoing teacher training and effective communication between schools and parents are essential. This study recommends differentiated instruction as an inclusive and adaptive learning strategy to support the optimal development of early childhood learners.